The Innovative Educational Ecosystem of the University as an Enhancing Factor in the Quality of Professional Training (Journal of Educational Sciences, 2026)
The article is devoted to the analysis of the process of forming an innovative educational ecosystem at a leading Kazakhstan university in the context of digital modernization and the innovative development of higher education.The study examines the perceptions of students, faculty members and employers regarding the key elements of the innovative educational ecosystem and their influence on the development of graduates’ professional, digital and communicative competencies.The empirical part of the study is based on focus group discussions involving students of different educational levels, faculty members and representatives of employers. The qualitative data analysis made it possible to identify both common requirements for the educational environment and specific expectations of individual stakeholder groups. Particular attention is paid to the «students as partners» approach, the integration of practice-oriented learning, mentoring, digital tools and feedback mechanisms, as well as the role of digital infrastructure in competency development.The results indicate a high demand for aligning educational practices with the objectives of innovative development, increasing stakeholder engagement and adopting a comprehensive approach to designing the educational ecosystem. The study’s conclusions are aimed at improving the university educational environment, developing students’ competencies and enhancing the competitiveness of graduates in the labor market.Keywords: innovative educational ecosystem, digital transformation, graduates’ competencies, student-centered learning, competency-based approach, focus groups, practice-oriented learning, employer engagement.